Studies on hardened properties of concrete incorporated with copper slag. (2022) - Kumar, Asha; Tejaswini, M.L.
Abstract: The present study aims to develop sustainable construction aggregates using industrial solid waste material like copper slag which is produced from smelting and refining process of copper. Copper slag contains Fe2O3 [35–60%] and SiO2 [25–40%] apart from small amounts of CaO, Al2O3 and CuO which makes it a potential solid waste material to be used as replacement to conventional fine aggregates. In this study, an attempt has been made to utilize copper slag as alternative to conventional fine aggregates in engineered way by conducting mix proportioning for M20, M25, M30, M35 and M40 grade of concrete. Initially the dosage of super plasticizer i.e., 0.75% is fixed to get the required workability of 75–100 mm by performing various trials. The water to cement ratio for each grade of concrete was found by trial and error method using the ratios 0.4, 0.42 and 0.44. This paper also studies the corrosion behaviour of steel reinforcement embedded in copper slag concrete. Corrosion of steel reinforcement is one of the major causes affecting the long-term performance of reinforced-concrete structures. Hence, the corrosion test was conducted by using thermo mechanical treatment (TMT) steel of 150 mm length and 8 mm diameter which are embedded in concrete cube of size 150 mm × 150 mm × 150 mm. On completion of accelerated corrosion, all the concrete samples were removed from all the connections and taken out of tank. Further for reinforced concrete with 40% replacement of copper slag, the percent of decrease in compressive strength is on lower side for nominal concrete as compared to concrete with copper slag. All the concrete specimens were subjected to wetting and drying in alternate way by placing in 3.5% NaCl solution. The findings in the study demonstrate that copper slag addition contributes to less resistance to corrosion attack.